Study Kelayakan Usaha Ternak Sapi Dengan Pemanfaatan Limbah Kelapa Sawit Di PT. Citra Borneo Indah Kalimantan Tengah - Risca Permatasari (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2015)
The purpose of the study entitled "Feasibility Study Cattle with Palm Oil Waste Utilization in PT. Citra Borneo Indah Central Kalimantan" is to analyze the financial feasibility of animal feed processing business with oil palm waste material and analyze the financial feasibility of the cattle business using the feed with oil palm waste material. This research was conducted in Sulung Ranch which is a subsidiary of PT.Citra Borneo Indah engaged in animal husbandry.Object of this study is the cost of investment, operating costs, production, and reception. Captured data is monthly from 2011 to 2013. Collecting data by observation, and interviews. The analytical method used is the analysis of the table, and a financial analysis of business which include NPV, IRR, BCR, and PP. The results of this research are animal feed processing business with the use of palm oil waste to develop. Cattle business with the use of palm oil waste worth to be developed.Keyword: Waste palm oil, cattle, feasibility study